A Rare Epilepsy Type: Eating Epilepsy - Zeynep ÖZÖZEN AYAS; Ayhan BÖLÜK (Archives of Epilepsy, 2017)

(untitled)
Eating epilepsy is a rare type of reflex epilepsy. Genetic factors, types of food, and eating habits are important. Presently described is case of a 28-year-old man with simple partial and secondary generalized epilepsy, provoked especially by fatty or starchy foods. Neurological examination and laboratory tests were normal. Active epileptiform discharges were not detected on electroencephalography; however, cranial magnetic resonance imaging revealed left parietal encephalomalacia. The patient’s seizures were controlled with appropriate dosage of oxcarbazepine and levetiracetam. As this case is extremely rare type of reflex epilepsy, presentation is accompanied by review of the literature.